2022
DOI: 10.1021/jacs.2c01760
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Double-Stranded DNA-Based Nanostructure Folded by a Covalently Bivalent CRISPR/dCas System

Abstract: DNA nanotechnology has been widely employed in the construction of various functional nanostructures. However, most DNA nanostructures rely on hybridization between multiple single-stranded DNAs. Herein, we report a general strategy for the construction of a double-stranded DNA–ribonucleoprotein (RNP) hybrid nanostructure by folding double-stranded DNA with a covalently bivalent clustered regularly interspaced short palindromic repeats (CRISPR)/nuclease-dead CRISPR-associated protein (dCas) system. In our desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…Thus, the in vivo administration of these systems for clinical gene therapy is awaited. Wu et al 133 reported a broad technique for constructing a dsDNA-RNP fused nanostructure by folding dsDNA with a CRISPR/dCas9/12a system. They fused dCas9 and dCas12a via a stimuli-responsive peptide linker.…”
Section: Nanostructure-based Nanocomposites For Delivery Of Crispr/ca...mentioning
confidence: 99%
“…Thus, the in vivo administration of these systems for clinical gene therapy is awaited. Wu et al 133 reported a broad technique for constructing a dsDNA-RNP fused nanostructure by folding dsDNA with a CRISPR/dCas9/12a system. They fused dCas9 and dCas12a via a stimuli-responsive peptide linker.…”
Section: Nanostructure-based Nanocomposites For Delivery Of Crispr/ca...mentioning
confidence: 99%
“…They fold double‐stranded DNA with a covalently bivalent between dCas9 RNPs and dCas12a RNPs to codeliver the dCas9 and dCas12a systems. [ 89 ]…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…CRISPR (clustered regularly interspaced short palindromic repeats) system as a powerful gene editing tool has been considered as an excellent signal amplification strategy for the development of biosensing field. This system consists of CRISPR-associated proteins (Cas) and related guide CRISPR RNA (crRNA). Notably, the newly founded CRISPR/Cas12a trans-cleavage activity, namely, Cas12a and its corresponding CRISPR RNA (crRNA; Cas12a/crRNA duplex), can specifically recognize and cleavage specific DNA based on the recognition of protospacer adjacent motif (PAM) sequence, , which endows CRISPR/Cas12a with remarkable signal amplification ability and precise specificity. , A CRISPR/Cas12a-based ratiometric fluorescent sensor has been constructed by digesting TAMRA-labeled DNA with Burkholderia pseudomallei (Bp) DNA activated CRISPR/Cas12a for Bp DNA detection, and human papilloma virus (HPV-16)-activated CRISPR/Cas12a has been used to increase the photocurrent of Nd-doped BiOBr nanosheets for sensitive detection of HPV-16 . The HPV-16 activated CRISPR/Cas12a has also been used to cleave off methylene blue (MB)-labeled ssDNA from electrode surface for electrochemical biosensing of HPV-16 .…”
Section: Introductionmentioning
confidence: 99%